(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The use of product placements hasevoked interest by marketers for many years. Yet, little research has been doneon this medium within the South African context; therefore the purpose of thisstudy is to investigate consumer attitudes towards prominent product placementsand the principal actor using the brand in the film or broadcast programme.Product placements are seen as a subtle means of advertising that should beused in conjunction with the traditional mass media. It has been used for manyyears and can be defined as the compensated inclusion of a branded product orbrand identifiers, through audio and/or visual means within mass mediaprogramming (films and broadcast programmes) for promotional purposes. Thesurvey method entailed that respondents had to observe a series of scenes froma film clip containing product placements; thereafter they were required tocomplete a questionnaire. Two hundred respondents, between the ages of 18 to 24participated in this survey. Results indicated that their ability to recallprominently placed products is greater than their ability to recall subtlyplaced products. It further indicates that a principal actor using a brand in afilm or broadcast programmes does not necessarily influence consumers’affective behaviour. It is suggested that product placements will become astrategic and viable marketing option in the mobile environment for targetingspecific groups. Advertising companies seek more venues for products. Fromthese findings it can be concluded that if marketers and advertisers considerproduct placements as an integrated marketing communication vehicle, they mustrequest that their brands are placed prominently in a film and broadcastprogrammes to ensure maximum exposure and greater awareness among consumers.The results also provide useful insight to media planners as to whether productplacement is effective when the principal actor uses it.